The Marshall Plan today : model and metaphor - Agnew, John A.; Entrikin, J. Nicholas, 1947- (Routledge studies in geopolitics., 2004)
This book goes beyond diplomatic history to place the Marshall Plan in the context of both the political economy of late 20th century Europe and the impact of American models of business and government that came with the Plan.